Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-17T18:15:25+01:00
A) 7x=4-8
7x=-4/7
x=-4/7

b) -2x=-13-3
-2x=-16//(-2)
x=8

c) -5x=32-4
-5x=28/*(-1)
5x=-28//5
x=-5 i 3/5

d) 13x=21-2
13x=19//13
x=1 i 6/13

e)3(x+2)+5x=(-8)
3x+6+5x=-8
8x=-8-6
8x=-14//8
x=-1i 3/4

f)2(x-3)-4(x+1)=2
2x-6-4x-4=2
-2x=2+6+4
-2x=12//-2
x=-6
2010-02-17T18:16:02+01:00
7x+8=4
7x=4-8
7x=-4/7
x=4/7

-2x+3=(-13)
-2x=-10
x=5

4-5x=32
5x=32-4
5x=28
x=5 3/5

13x-2=21
13x=21+2
13x=23
x=1 10/13


3(x+2)+5x=(-8)
3x+6+5x=-8
8x=-8-6
8x=-14
x=1 6/8


2(x-3)-4(x+1)=2
2x-6-4x-4=2
-2x=2+6
-2x=8/-2
x=-4
2010-02-17T18:18:07+01:00
A)7x+8=4/-8
7x=-4/:7
x=-4/7

b)-2x+3=-13/-3
-2x=-16/:(-2)
x=8

c)4-5x=32/-4
-5x=28/:(-5)
x=-5,6

d)13x-2=21/+2
13x=23/:13
x=23/13=1 10/13

e)3(x+2)+5x=-8
3x+6+5x=-8
8x+6=-8/-6
8x=-14/:8
x=1,75

f)2(x-3)-4(x+1)=2
2x-6-4x-4=2
-2x-10=2/+10
-2x=12/:(-2)
x=-6